Additional records and poorly known species of Kamimuria Klapálek, 1907 (Plecoptera, Perlidae) from southern China - Li, Kefan; Wang, Bingli; Bozdoğan, Hakan; Li, Weihai (Zootaxa, 2023)
Two poorly known species of Kamimuria Klapálek, 1907 originally known from southern China, K. melli Wu, 1935 and K. taoi Wu, 1936, are rediscovered and amended with supplementary descriptions of the aedeagi. Kamimuria atra Sivec & Stark, 2008 is recorded for the first time from China. Kamimuria liui (Wu, 1940) is newly recorded from southern China, amended with descriptions of the aedeagus and noted morphological variability, and compared to related congeners. Digital micrographs of the adult male, including the fully extruded aedeagi, are presented for the first time for the above four species.